Creating a Smart Generation by Improving the Quality of Education through Reading Literacy at SDN 5 Sudaji - Sukmawati, A.A. Komang Melia; Widayanti, Gusti Ayu Neta Putri; Widiantari , A.A.Ayu Mirah; I Gede Agus Julio Pramana; Trisnayani, Ni Nyoman Ayu; Werang, Basilius Redan (Formosa Journal of Applied Sciences, 2024)
This research aims to explore students' reading interest at SDN 5 Sudaji, Buleleng, as well as providing efforts that can be made to increase students' reading interest at this school. This research uses a descriptive qualitative approach with observation, interview and data triangulation techniques. Data analysis is carried out through an interactive model which includes data collection, data reduction, data presentation and drawing conclusions. The informants in this research were students at SDN 5 Sudaji, Buleleng, which is close to where the researcher lives. The research results show that students' interest in reading at SDN 5 Sudaji is still low. As a solution, researchers offer the school literacy movement (GLS) which includes providing library services in schools, reading corners in class, and holding competitions in schools. Apart from that, efforts to increase students' interest in reading in the family environment are also discussed.